Corrigendum to “A new hypothesis on the evolution of the hybosorid beetle capacity to conglobate their bodies into a tight ball (Coleoptera: Scarabaeoidea)” - Grebennikov, Vasily V.; Smith, Andrew B.T. (Fragmenta entomologica, 2022)
Corrigendum to “A new hypothesis on the evolution of the hybosorid beetle capacity to conglobate their bodies into a tight ball (Coleoptera: Scarabaeoidea)”